1999
DOI: 10.1177/0276146799192005
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequity and Quality of Life: A Macromarketing Perspective

Abstract: Consumption inequities have been explored within the consumer behavior and public policy literatures in marketing, but few investigations within these domains have examined their global dimensions. To help fill this gap, the authors investigate the gender aspects of consumer inequality worldwide using measures of quality of life at the societal level. After a brief introduction, a discussion of the theoretical foundation of our work and the measures used to examine inequities between men and women are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…According to Elizabeth Chin, the widespread dissemination of marketing messages within contemporary consumer societies creates the illusion of availability that does not exist for many citizens. Much recent scholarship has revealed that a variety of groups are left out of the material abundance that is available within the larger society, due, in part, to their race, gender, and/or relative poverty (e.g., Hill and Dhanda; Hill and Adrangi). This context is consistent with the perspective of Oscar Lewis, who first proposed the culture of poverty thesis ( Five Families ).…”
Section: The Culture Of Poverty Thesismentioning
confidence: 99%
“…According to Elizabeth Chin, the widespread dissemination of marketing messages within contemporary consumer societies creates the illusion of availability that does not exist for many citizens. Much recent scholarship has revealed that a variety of groups are left out of the material abundance that is available within the larger society, due, in part, to their race, gender, and/or relative poverty (e.g., Hill and Dhanda; Hill and Adrangi). This context is consistent with the perspective of Oscar Lewis, who first proposed the culture of poverty thesis ( Five Families ).…”
Section: The Culture Of Poverty Thesismentioning
confidence: 99%
“…Notwithstanding the publicized methodology of many of these rankings, their reliability or for that matter, accuracy, have been questioned in various studies (Boller 1966;Hill and Dhanda 1999). Studies in QoL utilize a list of relevant dimensions, assign importance weights to each of them, and try to quantify each dimension and then calculate a formulaic sum to signify the areas' QoL.…”
Section: Other Problems With Qol Measuresmentioning
confidence: 99%
“…Shopping "properly" may hold particular parlance for disabled women (Hill & Dhanda, 1999) whose access to the physical marketplace maybe difficult, if not impossible, without the assistance of other family members, or formalised care services. Therefore they are likely to experience a heightened sense of vulnerability (e.g.…”
Section: Consumer Vulnerability Identity and Transformationmentioning
confidence: 99%